Expression and Characterization of Chandipura Virus Proteins - Kumar, Kapila; Rana, Jyoti; Guleria, Ayushi; Gupta, Amita; Chaudhary, Vijay K.; Gupta, Sanjay (Research in Biotechnology, 2011)
Chandipura virus (CHPV) has recently emerged as an extremely lethal human pathogen in the family Rhabdoviridae and is linked to significant encephalitis outbreaks in different parts of India. The biology of CHPV remains less studied to date and the availability of reagents such as purified proteins can enhance research in this direction. In this study, we have overexpressed four of the CHPV proteins namely Nucleoprotein (N), Phosphoprotein (P), Matrix protein (M) and Glycoprotein (G) using threeÃ‚Â distinct tags in bacterial system and with changes in inducer concentration, growth and solubilisation conditions successfully purified M and G proteins for the first time along with N and P. Furthermore, the interactions of CHPV M protein with other viral proteins (G, N and P) was investigated using ELISA and GST pull down assays to show the utility of olubilised proteins. The results of both the assays demonstrated that M protein interacts with both G and N proteins, while it does not interact with P protein, in a similarÃ‚Â manner as reported for Vesicular Stomatitis Virus.